How Teachers Meet in Interdisciplinary Teams: Hangouts, Distribution Centers, and Melting Pots. (August 2020) - Meeuwissen, Stephanie N.E.; Gijselaers, Wim H.; Wolfhagen, Ineke H.A.P.; oude Egbrink, Mirjam G.A.
Abstract : Purpose: To explore team learning processes among interdisciplinary teacher teams in the development of integrated health professions education and to investigate students' perspectives on the quality of the educational courses. Method: Using an exploratory, sequential mixed-methods design, the first author conducted 17 vignette-guided, semistructured interviews with teachers originating from diverse disciplines. These teachers worked in different courses of integrated, undergraduate health professions programs at the Faculty of Health, Medicine and Life Sciences, Maastricht University, the Netherlands. The interview guide and vignettes were based on team learning research. The interviews sought to establish how interdisciplinary teacher team members work together on integrated curricula. The vignettes reflected constructs of team learning processes: sharing, co-construction, and constructive conflict. Data were collected between November 2017 and March 2018 and analyzed using template analysis. Sequentially, course evaluation data were used to provide a descriptive analysis of students' perspectives on educational quality (course organization, structure, learning effect, and alignment). Results: Three team approaches were identified. In fragmented teams or "hangouts, " teachers individually worked on tasks that they were interested in, leaving their disciplinary mark. Framework-guided teams or "distribution centers" aimed to work within the given frameworks and organizational expectations, striving for disciplinary balance. Integrated teacher teams or "melting pots" used an interdisciplinary approach on all topics and put students at the center. Integrated teams reflected high-level team learning processes and were most satisfied with their (team)work. In contrast, fragmented and framework-guided teams mainly reflected low-level team learning processes. Students evaluated courses of integrated teacher teams highest on all investigated quality items (course organization, structure, learning effect, and alignment). Conclusions: Successful interdisciplinary teacher teams are represented by an integrated approach with high-level team learning behavior and the best course evaluations. Therefore, health professions education management should actively encourage and facilitate integrated teacher teamwork. Abstract : Supplemental Digital Content is available in the text.